University Distance Education in Prisons as a Tool for Rehabilitation and Social Inclusion - Gina López-Armijos; Laura Ponce de León Romero (Social Sciences)
Many countries use the deprivation of liberty as a punitive strategy to ensure citizen security. Nowadays, a rehabilitative perspective has also been included to promote social inclusion. University education is a potential tool for achieving this goal. The aim of this article is to gather the opinions of twenty students and ten professors concerning the realities of university education in an Ecuadorian prison. This study uses an onto-epistemological approach and concentrates on the perception of individuals, employing a qualitative methodology. The results show that these educational programs have positive effects on the students, improving their life projects, their behavior inside and outside jail, and their digital knowledge and ICT skills, reducing recidivism and promoting labor market reintegration. The conclusions suggest that university distance education is a tool for rehabilitation and social inclusion and that greater involvement is required on the part of the State, companies, and the community in general to facilitate the graduates’ labor reintegration, as well as follow-up and social support services for ex-offenders and their families.